ANSWER and EXPLANATION
To show that the point given (5, -4) is a solution to the system of equations, we have to substitute the x and y values into both equations and check if the left-hand sides are equal to the right-hand sides.
For the first equation:
![\begin{gathered} 3(5)-2(-4)=23 \\ 15+8=23 \\ 23=23 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kxdjsh6g1jemzqedsda1c9jfh97ofq3318.png)
The left and right sides are equal.
For the second equation:
![\begin{gathered} 2(5)+(-4)=6 \\ 10-4=6 \\ 6=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fi0uhn2966p6kij8ntsrdcqjmdli29cf2b.png)
The left and right sides are equal.
Since the left and right sides of both equations are equal, then, (5,-4) is a solution to this system of equations.